Tumor Lysis Syndrome Induced by the R-ICE Regimen in a Patient with Non-Hodgkin Lymphoma: A Case Report - Gede Agung Setya Wibawa; Ni Made Renny Anggreni Rena (PT Dexa Medica, 2026)
Tumor lysis syndrome (TLS) is a life-threatening oncological emergency characterized by the massive release of intracellular metabolites. While common in acute leukemia, TLS is relatively rare in non-Hodgkin lymphoma (NHL) unless associated with high tumor burden. This case highlights a rare occurrence of severe TLS following the R-ICE (rituximab, ifosfamide, carboplatin, and etoposide) regimen in an NHL patient. A 64-year-old female diagnosed with NHL presented with bulkydisease. Following the second day of the R-ICE regimen, she developed decreased consciousness and acute kidney injury (AKI). Clinical findings included refractory hypotension and signs of a systemic inflammatory response. Based on theCairo-Bishop criteria, the patient was diagnosed with grade III TLS, complicated by hyperuricemia, hyperphosphatemia, and compensated metabolic acidosis. Emergency management included aggressive fluid resuscitation (0.9% NaCl2,500–3,000 ml every 8 hours), oral allopurinol (300 mg daily), and electrolyte monitoring. Hemodialysis was indicated but could not be performed due to hemodynamic instability and suspected concurrent nosocomial sepsis. Despite intensive supportive care and empirical antibiotics, the patient succumbed to multiorgan failure on the seventh day of hospitalization. This case underscores that TLS can occur in NHL patients undergoing salvage regimens like R-ICE. Clinicians must maintain a high index of suspicion for TLS and secondary sepsis, even in non-leukemic malignancies. Early aggressive hydration is vital, but hemodynamic stability remains a critical limiting factor for definitive renal replacement therapy.